A whole blood-based functional assay to characterize immunoglobulin A effector functions - Alice Bacon; Celia Cartagena García; Karin A. van Schie; René E. M. Toes; Jean-Marc Busnel (Taylor & Francis Group, 2024)
AbstractMost investigations on the immune cell-activating potency of IgA used purified total IgA and/or specific isolated cell populations. As IgA2 has been reported to be more pro-inflammatory than IgA1, we aimed to employ a fast and convenient whole blood-based assay to individually probe the capacity of the two IgA subclasses to activate immune cells in close physiological conditions. To this end, whole blood from healthy donors (n = 10) was stimulated with immobilized IgA1, IgA2m1 or IgA2m2 (the two main allotypic variants of IgA2). Activation of major leukocyte subsets was measured using a 10-color flow cytometry panel providing access to the expression of 5 activation markers on 6 different immune cell subsets. While capturing some heterogeneity of responses among donors, IgA2m1 and IgA2m2 systematically showed a stronger activation profile compared to IgA1 in a variety of dimensions. For example, both IgA2 allotypes led to stronger modulations of CD54, CD11b, CD62L, CD66b or CD69, on both or either monocytes or neutrophils, indicating a more pronounced pro-inflammatory effect for this subclass than IgA1. By taking into account donor-specific soluble and cellular components this whole blood-based functional approach provides new perspectives to further investigate IgA effector functions in mechanistic studies and/or translational research.